The social contagious effects of violent video game play: retaliatory, displaced, and the mere observation of aggression - Martin Delhove; Tobias Greitemeyer (Social Influence, 2023)
ABSTRACTAggression and violence have been shown to spread among connected individuals. The present experimental study aims to test whether exposure to violent video games increases aggression levels in players and whether this increased aggression spreads among their social network. Results showed that aggression after video game play is indeed contagious and that not only victims of the player’s aggression retaliate or are aggressive toward a neutral person (i.e., displaced aggression), but that even mere observers of the player’s aggression are aggressive toward a neutral person. Overall, our findings suggest that violent video game exposure may not only have an impact on the player’s level of aggression, but also on people who are connected to the player.